2019
DOI: 10.1002/app.47919
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of starch‐based films reinforced by ramie nanofibers (Boehmeria nivea)

Abstract: In this study, the use of cellulose nanofibers from ramie, a plant species with important characteristics of reinforcement, was investigated in the production of bio-based polymer films. A central composite rotatable design was applied to produce the films, analyze the effects of cassava starch, glycerol, and nanofibers content on their properties, obtain mathematical models, response surface plots, and determine an optimum composition. The films produced were characterized by mechanical properties, water vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
7
2
Order By: Relevance
“…Caetano et al 39 showed a large and significant increase in film thickness from 124 μm to 193 μm when amount of oil increased from 0 to 2% (w/v). Other authors have also reported the increment in thickness adding extracts and fibers 1,11,40–42 …”
Section: Resultsmentioning
confidence: 92%
“…Caetano et al 39 showed a large and significant increase in film thickness from 124 μm to 193 μm when amount of oil increased from 0 to 2% (w/v). Other authors have also reported the increment in thickness adding extracts and fibers 1,11,40–42 …”
Section: Resultsmentioning
confidence: 92%
“…The low water-contact angle of control films with nanofiber cellulose and films without the TTO and nanofiber cellulose was due to the cassava starch amylases’ chemical affinity with water [ 171 , 172 ]. Actually, the cellulose fibers were less hygroscopic than starch, which led to the weakening of the amylaceous matrix hydrophilicity, and therefore the film solubility [ 173 ]. Despite the oils’ lipidic characteristics, the solubility of films with TTO was somewhat more substantial than the solubility of control films (nanofiber cellulose).…”
Section: The Rationale Of Encapsulation Of Essential Oils Into Polymeric Nanofibersmentioning
confidence: 99%
“…Natural polysaccharides have received increased attention due to their renewability, biodegradability and film-forming properties [ 2 ]. Marques et al prepared cassava starch-based films that can be used for packaging in the food industry [ 3 ]. The calcium alginate film loading ciprofloxacin potentially healed infected foot ulcers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%